Prácticas de enseñanza de iniciación a la lecto-escritura en inicial II del Centro Educativo My Honey Kids de Quito. - Carate Miño, Carla Jeaneth (2015)
This research shows an overview on the teaching of reading and writing in primary education, the contributions are presented based on an analysis of teaching practice in the area of literacy, in the classroom of 4-5 years to 10 students of the School Kids My Honey in Quito. The observation period was conducted during the months of May and June 2015. The research was conducted according to the following aspects: planning, methodology, classroom activities and evaluation. This paper shows titration data collected through three instruments were: observation sheet, field diary and interviews to support the pedagogical approach of analysis. Through these instruments are collected and analyzed information for the work done in the classroom, the teacher in charge of initial II and the teaching-learning process in the field of literacy. It seeks to identify the pedagogical conditions and consolidate educational proposals to help improve teaching strategies.